2000
DOI: 10.1074/jbc.m000874200
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and Characterization of a 72-kDa Inositol-polyphosphate 5-Phosphatase Localized to the Golgi Network

Abstract: The inositol-polyphosphate 5-phosphatase enzyme family removes the 5-position phosphate from both inositol phosphate and phosphoinositide signaling molecules. We have cloned and characterized a novel 5-phosphatase, which demonstrates a restricted substrate specificity and tissue expression. The 3.9-kb cDNA predicts for a 72-kDa protein with an N-terminal proline rich domain, a central 5-phosphatase domain, and a Cterminal CAAX motif. The 3.9-kilobase mRNA showed a restricted expression but was abundant in test… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
110
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 94 publications
(113 citation statements)
references
References 46 publications
3
110
0
Order By: Relevance
“…Full-length or truncated SHIP-1 protein was immunoprecipitated (anti-SHIP-1 Ab; Santa Cruz Biotechnology) and incubated with 32 P-labeled PI (3,4,5)P 3 for 30 min in assay buffer (20 mM HEPES [pH 7.5], 5 mM MgCl 2 , 1 mM EGTA), as described (18).…”
Section: Measurement Of Ship-1 Phosphatase Activitymentioning
confidence: 99%
“…Full-length or truncated SHIP-1 protein was immunoprecipitated (anti-SHIP-1 Ab; Santa Cruz Biotechnology) and incubated with 32 P-labeled PI (3,4,5)P 3 for 30 min in assay buffer (20 mM HEPES [pH 7.5], 5 mM MgCl 2 , 1 mM EGTA), as described (18).…”
Section: Measurement Of Ship-1 Phosphatase Activitymentioning
confidence: 99%
“…The identity of PtdIns(3,5)P 2 was verified as described previously (25). No hydrolysis of PtdIns(3,5)P 2 was detected using purified recombinant enzyme.…”
Section: Characterization Of the Intracellular Localization Of Skip-mentioning
confidence: 99%
“…32 P-Labeled PtdIns(3,4,5)P 3 and PtdIns(3,5)P 2 were synthesized, and the 5-phosphatase assays were performed using purified His-tagged recombinant SKIP or the His tag alone as described (25,26).…”
Section: Transient Expression Of Gfp-or Ha-tagged Skip/skich and Skicmentioning
confidence: 99%
“…An alternative splice variant of Inpp5E that lacks the 34 amino acid region that contains the ITAMs has been described ( Figure 2). 37,81 Inpp5E is known to be tyrosine phosphorylated by activated insulin receptor 82 and Ser/Thr-phosphorylated by Aurora kinase A (AurkA). 83 In addition to hydrolyzing the product of PI3K enzymatic activity, it has been reported that Inpp5E interacts with p85 subunit of PI3K, negatively regulating the Akt pathway, and also binds Insulin receptor substrate 2(IRS2).…”
Section: Inositol Polyphosphate-5′ Phosphatase E: Inpp5ementioning
confidence: 99%
“…46 However, the role of this interaction in protein targeting is not clear. Indeed, it has been demonstrated that the N-terminus PRD of Inpp5E is sufficient to localize it to the Golgi, 46,81 suggesting that Rab20 binding is not the main factor for Inpp5E targeting. In proliferating cells, Inpp5E localizes at the trans-Golgi network 81 while in quiescent cells, Inpp5E localizes to the primary cilium.…”
Section: Inositol Polyphosphate-5′ Phosphatase E: Inpp5ementioning
confidence: 99%